2020
DOI: 10.2478/aoas-2019-0078
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Composition of Domestic Soybean Seeds and the Effects of Partial Substitution of Soybean Meal by Raw Soybean Seeds in the Diet on Pigs’ Growth Performance and Pork Quality (M. Longissimus Lumborum)

Abstract: The objective of the study was to determine the effect of replacing soybean meal with 5% of raw soybean seeds on the growth, feed consumption and utilization of growing pigs, also the carcass and pork quality. The growth experiment was conducted on 120 pigs of approx. 18.5 kg allocated to two dietary treatments. The animals from the control treatment (CON) were offered a diet with soybean meal, and the experimental group (EXP) was given 5% raw soybean seeds (NON-GMO, Augusta var.) instead of SBM. The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
2
10
1
Order By: Relevance
“…That result could be explained by the fact that pigs on the SBM diet had higher body weights at slaughter. On the contrary, Zaworska et al [ 7 ] recorded a reduced back fat thickness, however, the pig body weight at slaughter was lower in their study than here. Considering the physicochemical assessment of meat, a significant difference in the acidification of muscle tissue 45 min post mortem was observed between the gilts and barrows.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…That result could be explained by the fact that pigs on the SBM diet had higher body weights at slaughter. On the contrary, Zaworska et al [ 7 ] recorded a reduced back fat thickness, however, the pig body weight at slaughter was lower in their study than here. Considering the physicochemical assessment of meat, a significant difference in the acidification of muscle tissue 45 min post mortem was observed between the gilts and barrows.…”
Section: Discussioncontrasting
confidence: 92%
“…Moreover, the imported non-genetically modified SBM is considerably more expensive compared to a GMO SBM. Therefore, research on the possibilities of replacing GMO soybean meal in the nutrition of monogastric animals, particularly pigs, gallinaceous poultry, and waterfowl, has been performed [ 2 , 3 , 4 , 5 , 6 , 7 ]. In the past, the use of legumes, mainly lupin in monogastric animal nutrition, was limited due to high alkaloid contents that negatively affect growth, feed intake, and nutrient utilization [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, soybean meal mainly comes from genetically modified plants, which arouses objections in some consumers. Replacing soybean meal with protein feeds of local origin, not GMOs, is a pro-consumer activity, but also protects the domestic feed market, and in several cases had no negative effects on pig performance [ 3 , 4 , 5 , 6 ]. Besides legume seeds and rapeseed, corn dried distillers grains with solubles (cDDGS) are a good solution for replacement of soybean meal.…”
Section: Introductionmentioning
confidence: 99%
“…Zmudzińska et al [ 33 ] demonstrated that feeding pigs with diets containing legume plants and extracted rapeseed meal does not affect the pork meat quality. Other authors [ 34 ] showed that the experimental diet with an addition of 5% of raw soybean seeds affected ( p < 0.05) meat color and also meat composition.…”
Section: Resultsmentioning
confidence: 97%